Influences of humic-rich natural materials on efficiencies of UASB reactor: A comparative study. (December 2021) - Wang, Qinghong; Jiang, Liangyan; Niu, Hao; Liang, Jiahao; Liu, Zhiyuan; Arslan, Muhammad; Gamal El-Din, Mohamed; Chen, Chunmao
Graphical abstract: Highlight: Peat soil and lignite were added in UASB to study phenolic wastewater treatment. Peat soil improved phenols degradation but lignite showed poor removal performance. Peat soil enhanced the secretion of EPS and F420 following higher phenols removal. Peat soil facilitated the growth of syntrophic fermentation bacteria and methanogens. Abstract: Two humic-rich natural materials namely peat soil and lignite were supplemented in up-flow anaerobic sludge blanket (UASB) bioreactors for the treatment of phenolic wastewater. Peat soil improved phenol degradation and resistance to shock load; ultimately, contributing to higher COD removal efficiency (83.3%), methane production (4532 mL d -1 ), and better reactor's stability. Accordingly, the amount of extracellular polymeric substances (EPS) and coenzyme F420 in sludge were increased to 1.3-fold and 2.5-fold, respectively, as compared to the control treatment. The addition of lignite however displayed poor phenol degradation and no effects on the secretion of EPS and F420 . The peat soil significantly influenced the microbial community structures, whereas the effect of lignite was inconspicuous. In the presence of peat soil, the abundance of syntrophic fermentation bacteria and methanogens was significantly increased. This study illustrates the potential use of peat soil in UASB for the treatment of phenolic wastewaters.